Kontribusi Keterampilan Bahasa Inggris Terhadap Efektivitas Komunikasi Darurat di Atas Kapal - Natriya Faisal Rachman Ryan; Femmy Asdiana; Wahyu Oktavia; Muhammad Zainul Arifin; Muhammad Razka; Fausta Okta Rakha Putra (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the contribution of English language skills to the effectiveness of emergency communications on board ships and to identify the most crucial language aspects in crisis situations. The study employed a library research method by reviewing and synthesizing various relevant sources, including international and national journal articles on maritime affairs and language education, Standard Marine Communication Phrases (SMCP) from the International Maritime Organization (IMO), maritime accident investigation reports from the International Maritime Organization (IMO) and the Marine Accident Investigation Branch (MAIB), and emergency communication training and procedure documents published during the 2015–2025 period. Sources were selected based on their relevance to maritime communications, shipping safety, and the use of English in emergency situations. Data were analyzed qualitatively using a descriptive-comparative approach through the process of identifying themes, grouping findings, and synthesizing across sources. The results showed that English language skills, particularly listening skills and mastery of standard Maritime English phrases (SMCP), have a very important contribution to the speed, accuracy, and effectiveness of emergency responses. Various incident reports indicate that limited English proficiency can lead to miscommunication, misinterpretation of commands, and delays in emergency response. Therefore, emergency scenario-based English training needs to be strengthened to support shipping safety and minimize the risk of accidents at sea.